2017
DOI: 10.1091/mbc.e16-04-0208
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulatory roles of Mff and Drp1 in E3 ubiquitin ligase MARCH5–dependent degradation of MiD49 and Mcl1 and control of mitochondrial dynamics

Abstract: In addition to their direct roles in mitochondrial fission, Mff and Drp1 act as regulatory factors and control mitochondrial fission and fusion through a Ub-dependent mechanism. The E3 Ub ligase MARCH5 is negatively controlled by Mff and Drp1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 76 publications
4
84
0
Order By: Relevance
“…The matrix protein, Hsp60, likewise did not undergo peroxisomal translocation following CCCP treatment (Fig B). It has been reported that Drp1, Fis1, Mitofusin (MFN) 1/2, MiD49, and Mcl1 interact with MITOL as substrates . We consequently also examined the subcellular localization of these proteins following CCCP treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The matrix protein, Hsp60, likewise did not undergo peroxisomal translocation following CCCP treatment (Fig B). It has been reported that Drp1, Fis1, Mitofusin (MFN) 1/2, MiD49, and Mcl1 interact with MITOL as substrates . We consequently also examined the subcellular localization of these proteins following CCCP treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The denaturing immunoprecipitation ( Fig. 7a) was adapted from [21]: Harvested cells were resuspended in denaturing buffer (1% SDS, 5 mM EDTA, 10 mM β-mercaptoethanol) and incubated at 100°C for 10 min. After centrifugation at 21,000 × g for 5 min to clear the lysate of insoluble debris the supernatant was diluted by addition of ten times its volume of immunoprecipitation buffer (20 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 0.5% NP-40, 5 mM N-ethylmaleimide, and protease inhibitors) and protein concentration was measured by Bradford analysis.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Human mutations in DRP1 or DYN2 have been associated with neurological impairments (Gonzalez-Jamett et al, 2014; Vanstone et al, 2016; Waterham et al, 2007). Drp1, despite lacking a transmembrane domain, cycles from the cytosol to spots on the mitochondrial outer membrane (Smirnova et al, 1998) by interacting with several proteins, including Fis1, Mff, MiD49, MiD51 and a BAR-domain protein endophilin B1 (Cerveny et al, 2001; Cherok et al, 2017; Fekkes et al, 2000; Gandre-Babbe and van der Bliek, 2008; Otera et al, 2010; Palmer et al, 2011; Tieu and Nunnari, 2000; Zhao et al, 2011). The mitochondrial receptors are suggested to regulate Drp1-mediated fission in response to other signals (Koirala et al, 2013; Lackner et al, 2009; Loson et al, 2014; Loson et al, 2013).…”
Section: Cellular Machinery Of Mitochondrial Fissionmentioning
confidence: 99%
“…More recently, Drp1 and its mitochondrial receptors have been linked to Bcl-2 family proteins in a different manner. Deletion of either Drp1 or Mff results in increased ubiquitination and degradation of MiD49 and the anti-apoptotic Bcl-2 family protein Mcl-1, which is mediated by E3 ubiquitin ligase MARCH5 located on the the outer mitochondrial membrane (Cherok et al, 2017). Drp1 is itself posttranslationally regulated by activating phosphorylation at Ser616 and inhibitory phosphorylation at Ser637.…”
Section: Cellular Machinery Of Mitochondrial Fissionmentioning
confidence: 99%